APPLICATION OF A VIRTUAL LABORATORY IN PHYSICS LESSONS (Innovative professional education, 2025)
The article is dedicated to the use of virtual laboratories in physics lessons as an effective tool for modeling physical phenomena and conducting experiments. The main advantages and disadvantages of such laboratories are discussed, with examples of their practical application, including the PhET Interactive Simulations platform. The challenges of implementing digital technologies into the educational process and the prospects for their development are outlined.
Keywords: virtual laboratory, interactive simulations, physical experiments, educational technologies, digitalization